Menganalisis Teori Permintaan, Penawaran dan Keseimbangan Pasar - Septia Najwa Lubis; Meme Syakira Rizky; Vicky Raudha Nafisa; Muhammad Arfan Harahap (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This paper discusses the concept of demand and supply, both from the perspective of conventional economics and Islamic economics. In conventional economics, the relationship between price and quantity of goods demanded or offered is explained through basic laws that are widely known. Several simple illustrations, such as the case of chili prices and children's clothes, are used to facilitate readers' understanding of the movement of the curve and market equilibrium. Meanwhile, in Islamic economics, the principle of demand and supply still applies, but is framed by sharia values ​​that emphasize justice, ethics, and social responsibility. Consumption and production are not solely directed at profit, but also consider aspects of usefulness and sustainability. Thus, Islamic economics offers an approach that is not only rational, but also morally charged.